Modified Capanna’s Technique (Vascularized Free Fibula Combined with Allograft) as a Single-Stage Procedure in Post-traumatic Long-Segment Defects of the Lower End of the Femur: Outcome Analysis of a Series of 19 Patients with an Average Gap of 14 cm - Dheenadhayalan Jayaramaraju; Hari Venkataramani; Raja Bhaskara Rajasekaran; Devendra Agraharam; Shanmuganathan Raja Sabapathy; Shanmuganathan Rajasekaran (Indian Journal of Plastic Surgery)
Objectives Salvage and reconstruction of posttraumatic defects of the long bone are complex due to the multiple procedures involved and increased chances of poor outcomes. We present the outcomes of the modified Capanna’s technique—a reliable single-stage procedure of combining allograft and free vascularized fibular graft—in treating large posttraumatic bone defects in the distal third of the femur. Study Design This is a retrospective analysis. Materials and Methods Between April 2012 and September 2016, 19 patients with an average age of 33.8 years (range: 18–49 years) and an average defect of 14.5 cm (range: 9.5–20 cm) in the distal femur were managed by the modified Capanna’s technique. Bone union time and functional outcome using lower extremity functional score (LEFS) after union were noted. Outcomes and Results Eighteen grafts went onto achieve bony union at an average of 6.6 months (range: 5–9), with an average knee flexion of 80 degrees (range: 45–110 degrees) and an average LEFS of 63 (range: 46–72). One patient had a nonunion with graft resorption at 8 months following persistent infection and was revised with debridement and augmenting the vascularized fibula from the other leg which went on to achieve union. Three patients had superficial infection, and three patients had delayed union. Conclusion The modified Capanna’s technique provided increased biology and enhanced structural stability and therefore is a good single-stage procedure in the reconstruction of posttraumatic long-segment defects of the distal femur. Level of Evidence Level 4. Level of Clinical Care Level I tertiary trauma center.